MENAKAR MASLAHAT OPERASI KELAMIN PERSPEKTIF HUKUM ISLAM - aris man (Hukum Islam, 2019)
AbstractHumans are unique creatures and never satisfied. Humans dissatisfaction consist of variety things, including their own physical conditions. This matter caused by the reality that humans are born with various advantages and their respective shortcomings. Some people are born with perfect physical conditions, with perfect genital organs as men or women (with one genital organ). But some of people are born with imperfect physique conditions, with multiple genital organs (penis and vagina), or have an imperfect genitals (have one sex but there are organs the sex is not perfect, so the sex is not clear). Though the clarity gender has a certain legal consequenses. In this case they motivated to do genital surgery. The genital surgery that tend to Tashih or Takmil (repair or refinement) is permitted but sex change is prohibited. This is because people born with abnormal genitals can experiencing psychological and social disorders so that they can be excluded and isolated from the lives of normal people and sometimes to find their own way, like prostitute themselves as transvestites or commit homosexuality and lesbianis.